MOTIVASI INDONESIA MELAKUKAN KERJASAMA DENGAN AUSTRALIA DI BIDANG EKONOMI DIGITAL - Maulida "; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study explains the motivation of Indonesia to collaborate with Australia in the field of digital economy. Increasing technological advances have changed human behavior in carrying out transactions both trade and financially. Indonesia's geographical conditions pose challenges in financial inclusion, Indonesia needs to learn a lot from Australia which has a more advanced financial technology infrastructure and a well regulated financial sector by the state.This study uses the perspective of liberalism in international relations and is supported by foreign policy theory, this study uses the concept of international cooperation. This research is qualitative research with descriptive analysis method. The scope of research is financial technology cooperation in the field of digital payments.The researcher made an answer stating that Indonesia's motivation to cooperate with Australia in the field of digital economy was because of the transfer of knowledge about financial technology which would have an impact on increasing the efficiency of payment instruments in electronic transactions.Keywords : Indonesia, Australia, Digital Economy, Financial Technology, Efficiency, E-commerce.